Functional properties of winged bean (Psophocarpus tetragonolobus) protein - Abareta, Roman Paul R.; Rumbaoa, Rowena Grace O. (c2011.)
ABSTRACT Protein extractability from dried winged bean (Psophocarpus tetragonolobus) seeds using pH and incubation time as variables were evaluated. The pH 10-60 min combination was selected for protein extraction because of good yield (21.16%), protein solubility, emulsion capacity (71.20 mL oil/g sample) and stability, and oil absorption capacity (8.53g oil/g sample). Proximate and physico-functional characteristics of the winged bean full-fat and defatted flours and the extracted protein were performed in comparison with isolated soy protein. All samples exhibited least solubility at their isoelectric pH of 4. Both proteins had comparable pH values (6.90 for winged bean and 6.89 for soy) which were higher than the flour samples. Proximate composition ranged from 7.01% to 13.6% for moisture, 8.92% to 15.40% for fat, 33.57% to 91.04% for protein, and 4.29% to 9.34% for ash for the four samples. Foaming (74.17% and 73.33% for winged bean and soy, respectively) and emulsion capacities (66.61 and 67.48 ml oil/g sample for winged bean and soy, respectively) were similar between proteins, although higher stabilities and wettability were exhibited by the former. Defatted winged bean flour had a significantly (p < 0.05) lower bulk density than the other samples. The protein samples exhibited satisfactory water- and oil-binding capacities. However, winged bean samples showed poor gelling capacity. Nonetheless, winged bean was found to be a good alternative protein source for food applications.
Thesis(BSFT)--University of the Philippines Diliman
Keywords: Winged bean